Interpretation of complex geological structures with the use of forward and inverse modeling of magnetotelluric field - WOJDYŁA, Marek; STEFANIUK, Michał (Geology, Geophysics and Environment, 2011)
General assumptions of 1D and 2D modeling and inversion were presented in this paper. Methodology of magnetotelluric data interpretation was described including analysis of dimensionality of geoelectrical medium and its influence on choosing the proper interpretation model. Relations between initial model and final results of inversion were shown based on magnetotelluric (AMT and CSAMT) data from Grabownica oil and gas field. The second example was from the Lodyna oil field. A possibility of interpretation of thin vertical layers, which can approximate the Lodyna field by 1D and 2D MT inverse procedures was analyzed. Dependences between final geological models and MT curve type (TE mode or TE mode) taken to interpretation were shown. Finally, methodology of interpretation was proposed.